A preliminary study of educational experiences that promote perceptions of college readiness in individuals from lower socioeconomic backgrounds interested in pursuing a career in science, technology, engineering, math, or medicine (STEMM) - Naik, Akshata R.; Davidson, Cameron J.; Hurse, Deidre N.; Kemp, Kyeorda (Frontiers in Education, 2024)
Introduction College readiness encompasses many different domains, including content knowledge, metacognitive skills, communication skills, learning strategies, and transitional knowledge. College readiness impacts academic achievement; moreover, student perceptions regarding college readiness impact their behavior and decision to attend college. High-achieving students from lower socioeconomic status (SES) areas possess grit and intelligence, but systemic barriers and inequities can interfere with the achievement of academic success in part due to reduced college readiness. Methods In this study, we explore if educational opportunities, such as outreach and pathway programs (OPP), Advanced Placement and International Baccalaureate, and college dual enrollment, impact perceptions of college readiness in a nationwide sample of 339 matriculating college students who wish to enter into Science, Technology, Engineering, Mathematics, and Medicine (STEMM) related fields. Results OPPs (p = 0.005) and dual enrollment (p = 0.002) are predictive of higher perceptions of college readiness. When individuals are partitioned into low and high SES by a median-split, OPPs (p = 0.015) and dual enrollment (p < 0.001) are predictive for students from low SES areas only. Conclusion This work indicates the importance of educational opportunities in improving perceptions of college readiness for students from low SES areas and potentially how resources may be better allocated in the future.